High-performance electrochemiluminescence sensors based on ultra-stable perovskite quantum dots@ZIF-8 composites for aflatoxin B1 monitoring in corn samples. (1st June 2023) - Wang, Qian; Xiong, Chengyi; Li, Jingwen; Deng, Qianchun; Zhang, Xiuhua; Wang, Shengfu; Chen, Miao-Miao
Highlights: An ingenious electrochemiluminescence (ECL) assay was developed for sensing. Methylamine perovskite quantum dots (MP QDs) wrapped by ZIF-8 had enhanced ECL. Good water-stability and enhanced ECL mechanism of MP QDs@ZIF-8 were investigated. Ultra-sensitive aflatoxin B1 (AFB1)-imprinted ECL sensors were constructed. The feasibility of this ECL sensor was verified in corn sample for AFB1 detection. Abstract: Aflatoxin B1 (AFB1) that is prone to contaminate corns brings a serious threat to human health. Therefore, it is of great significance to construct novel detection methods for AFB1 tracing. Here, methylamine perovskite quantum dots (MP QDs) encapsulated by ZIF-8 metal–organic frameworks (MP QDs@ZIF-8) were prepared and then ultra-stable electrochemiluminescence (ECL) sensors were developed. By the confinement of cavities structure, multiple MP QDs were crystallized and embedded inside ZIF-8 to form MP QDs@ZIF-8, achieving stable and robust ECL responds in aqueous environment. Further combined with AFB1-imprinted polymer, the constructed ECL sensor showed good selectivity and ultra-sensitivity (the detection limit was 3.5 fg/mL, S/N = 3) with a wide linear range from 11.55 fg/mL to 20 ng/mL for AFB1 quantification. Satisfactory recoveries in corn samples indicated the reliable practicability of the proposed sensor for AFB1 assay. This work provided a novel pathway in designing high-performance ECL sensing platform for food safety.